ECG-SYNCHRONIZED MYOCARDIAL PERFUSION TOMOSCINTIGRAPHY AND CARDIAC RESYNCHRONIZATION THERAPY - E. N. Ostroumov; E. D. Kotina; V. V. Slobodyanik; V. V. Tonkoshkurova; I. Yu. Tunyaeva; A. E. Ermolenko; D. V. Shumakov (Российский кардиологический журнал, 2011)
.